2014
DOI: 10.31254/phyto.2014.3504
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening, antioxidant activity, total polyphenols and flavonoids content of different extracts of propolis from Tekel (Ngaoundal, Adamawa region, Cameroon)

Abstract: Five extracts of propolis of Adamawa Cameroon were obtained by percolation and maceration with five different solvents: hexane, ethyl acetate, ethanol, methanol and water, in order of increasing polarity. Phytochemical screening was carried out on the extracts and the total content in flavonoids and polyphenols were evaluated by photometric methods. The total flavonoid content was evaluated using the Neu reagent (2-aminodiethyl diphenylborinate) and quercetin as standard and the results varied from 0.84±0.02 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The use of synthetic antioxidants is on a decline because compounds such as butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA) may have adverse effects and as a result, there is a need to identify alternative natural sources of food antioxidants [ 30 ]. Propolis extracts are consumed by people from different parts of the world in the form of alternative medicine, food complements and nutraceuticals since they have antioxidant properties and can contribute protect living tissues from cellular damage caused by oxidative agents and free radicals [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of synthetic antioxidants is on a decline because compounds such as butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA) may have adverse effects and as a result, there is a need to identify alternative natural sources of food antioxidants [ 30 ]. Propolis extracts are consumed by people from different parts of the world in the form of alternative medicine, food complements and nutraceuticals since they have antioxidant properties and can contribute protect living tissues from cellular damage caused by oxidative agents and free radicals [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58][59] The presence of reactive oxygen species and reactive nitrogen species in the human body can cause oxidative stress and related illnesses though they are useful in some physiological activity, but harmful when they are in excess. [60][61][62] Both plants can serve as natural antioxidants and food preservatives. G. cola has shown to more active and this good antioxidant activity of this plant has been reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…From our study, the reported quantities of phytochemicals and bioactivities are in accordance with those earlier reported. 4,[15][16][17][18][19] Previous studies on total phenols have been performed in different regions of the world, for example, in Algeria 0.8-9.0 mg GAE/g, 20 Mexico 68-500 mg GAE/g, 21 Spain 200-340 mg GAE/g, 22 Turkey 34.5-259.4 mg GAE/g 23 and on total flavonoids in Turkey 21.3-152.6 mg QE/g, and Mexico 13-379 mg QE/g, Algeria 0.6-3.5. All these results are consistent with our data, except for some variation because of the influence of vegetation on the chemical properties of propolis.…”
Section: Discussionmentioning
confidence: 99%